Migration, governance and violent exclusion: exploring the determinants of xenophobic violence in post-apartheid South Africa - Misago, Jean Pierre (My University, 2016)
Responding to inadequacies and limitations of current causal explanations for xenophobic violence which has become a long standing feature in post-Apartheid South Africa, this study proposes a Governance Model of Xenophobic Violence that provides a comprehensive empirically-based and theoretically informed causal explanation. It is a multivariate empirical and integrated theoretical explanatory model that identifies and explains the roles of - and the complex interplays between - the key determinants of xenophobic violence consisting of underlying causes, proximate factors and triggers. The six key determinants the model identifies are: deprivation, xenophobic beliefs, collective discontent, political economy, mobilization and governance. This study argues that these determinants and their interconnections in a value-added process constitute the necessary and sufficient conditions for the occurrence of xenophobic violence. I call it the governance model because of the predominant role governance plays in the occurrence of xenophobic violence. With underlying causes (deprivation, xenophobia and collective discontent) already established, the study pays particular attention to the often missed proximate factors and triggers (the political economy of the violence, mobilization and governance). It is through the findings on these new factors that the study introduces new empirical and theoretical insights and innovations to the understanding of, not only, xenophobic violence in South Africa but also collective violence generally. First, this study argues that xenophobic violence in South Africa is just ‘politics by other means and by doing so brings to the fore the often missed centrality of micro-politics and localised political economy factors as key drivers of collective violence particularly communal violence. Second, the study argues that that the triggers of xenophobic violence and of collective violence generally lie in the mobilization processes and not in the grievances and ensuing discontent as argued by many theoretical approaches to collective violence. The study suggests a new theoretical model, the Mobilization of Discontent Model, which captures the increasingly recognised centrality of mobilization as a trigger of collective violence. Third, the study argues that governance is a key determinant of xenophobic and collective violence but not necessary in ways often assumed or prescribed by time-honoured and widely accepted theoretical predictions, particularly those contending that collective violence and other forms of contentious collective action tend to occur in societies where mechanisms of social control have lost their restraining power. By demonstrating that local governance deliberately facilitated the occurrence of xenophobic violence in areas where it occurred by providing what I term micro-political opportunity structures, the study calls into question the common understating of the relationship between governance and collective violence and reveals some aspects of this relationship that are either misunderstood or undetected until now. The Governance Model of Xenophobic Violence this study proposes is an innovation that clearly illustrates the poverty of most explanatory models of collective violence, which makes it an appropriate tool for integrating empirical and theoretical knowledge from different disciplines and for identifying gaps in existing scholarship.
Dissertation in fulfilment of the requirements for the degree of Doctor of Philosophy (PhD) in Migration and Displacement Studies, School of Social Sciences, Faculty of Humanities, University of the Witwatersrand April 2016
Keywords: Xenophobia--South Africa; Immigrants--Violence against--South Africa; Refugees--South Africa; South Africa--History--1994-; South Africa--Race relations--21st century